Copper homeostasis - Burkhead, Jason L (The New phytologist, 2009)
Copper (Cu) is a cofactor in proteins that are involved in electron transfer reactions and is an essential micronutrient for plants. Copper delivery is accomplished by the concerted action of a set of evolutionarily conserved transporters and metallochaperones. As a result of regulation of transporters in the root and the rarity of natural soils with high Cu levels, very few plants in nature will experience Cu in toxic excess in their tissues. However, low Cu bioavailability can limit plant productivity and plants have an interesting response to impending Cu deficiency, which is regulated by an evolutionarily conserved master switch. When Cu supply is insufficient, systems to increase uptake are activated and the available Cu is utilized with economy. A number of Cu-regulated small RNA molecules, the Cu-microRNAs, are used to downregulate Cu proteins that are seemingly not essential. On low Cu, the Cu-microRNAs are upregulated by the master Cu-responsive transcription factor SPL7, which also activates expression of genes involved in Cu assimilation. This regulation allows the most important proteins, which are required for photo-autotrophic growth, to remain active over a wide range of Cu concentrations and this should broaden the range where plants can thrive